2022
DOI: 10.1007/s40136-022-00428-z
|View full text |Cite
|
Sign up to set email alerts
|

How to Manage Taste Disorders

Abstract: Purpose of the Review This study aims to summarize the current state of the art of how taste disorders are clinically best managed. Recent Findings Taste disorders are distressing for the concerned patients since eating and drinking become bothersome or impossible. Apart from nutritional problems, quality of life is impaired. Still, diagnosis and treatment of taste disorders are elusive, and general knowledge about taste and its affection is little within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Dysgeusia (metallic or distorted taste) was also identified in this systematic review and has also been reported in the literature [76]. Dysgeusia is generally a common symptom reported with various oral disorders, such as oral lichen planus, candidiasis, and taste disorders [77]. Hormonal changes in the menopausal period have been reported to be associated with dysgeusia [78].…”
Section: Other Findingsmentioning
confidence: 75%
“…Dysgeusia (metallic or distorted taste) was also identified in this systematic review and has also been reported in the literature [76]. Dysgeusia is generally a common symptom reported with various oral disorders, such as oral lichen planus, candidiasis, and taste disorders [77]. Hormonal changes in the menopausal period have been reported to be associated with dysgeusia [78].…”
Section: Other Findingsmentioning
confidence: 75%
“…We asked untreated patients upon consultation to report the presence of subjective taste impairment, reducing possible influence from recall inaccuracies. By controlling for the taste of the contralateral to the mass side of the tongue, we decrease the effect of confounding factors that could influence taste function bilaterally, such as age, gender, systemic disease, and medication (13,30). However, we cannot exclude other confounders influencing our results.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers utilized the following definitions [25] to categorize the taste changes reported by patients: normogeusia—no change in taste, including both the ability to identify flavors and the taste intensity; ageusia—complete loss of flavor perception; hypogeusia—reduced flavor perception; and parageusia—distorted taste perception, such as a switch from one flavor to another.…”
Section: Methodsmentioning
confidence: 99%